Erosión del suelo y gestión ambiental en condiciones mediterráneas - Rubio J.-L. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
In Mediterranean conditions hydric soil erosion is the most dangerous threat of soil degradation. The erosion processes have widespread consequences in the ecological values of the land and also strong implications in the agricultural and forest productivity as well as other socioeconomics effects (increase of risks and damage of flooding, damages in irrigation and communication infrastructures...). The most influencing bio-physical and human factors are discussed. Sound ecological guidelines or policy to control soil erosion are exposed.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)